Tranexamic acid by the intramuscular or intravenous route for the prevention of postpartum haemorrhage in women at increased risk: a randomised placebo-controlled trial (I’M WOMAN) - Amy Brenner; Haleema Shakur-Still; Rizwana Chaudhri; Projestine Muganyizi; Oladapo Olayemi; Monica Arribas; Aasia Kayani; Kiran Javid; Adenike Bello; Ian Roberts; on behalf of the I’M WOMAN Trial Collaborative Group (Trials, 2023)
Abstract Background Postpartum haemorrhage (PPH) causes about 70,000 maternal deaths every year. Tranexamic acid (TXA) is a life-saving treatment for women with PPH. Intravenous (IV) TXA reduces deaths due to PPH by one-third when given within 3 h of childbirth. Because TXA is more effective when given early and PPH usually occurs soon after childbirth, giving TXA just before childbirth might prevent PPH. Although several randomised trials have examined TXA for PPH prevention, the results are inconclusive. Because PPH only affects a small proportion of births, we need good evidence on the balance of benefits and harms before using TXA to prevent PPH. TXA is usually given by slow IV injection. However, recent research shows that TXA is well tolerated and rapidly absorbed after intramuscular (IM) injection, achieving therapeutic blood levels within minutes of injection. Methods The I’M WOMAN trial is an international, multicentre, three-arm, randomised, double-blind, placebo-controlled trial to assess the effects of IM and IV TXA for the prevention of PPH in women with one or more risk factors for PPH giving birth vaginally or by caesarean section. Discussion The trial will provide evidence of the benefits and harms of TXA for PPH prevention and the effects of the IM and IV routes of administration. The IM route should be as effective as the IV route for preventing bleeding. There may be fewer side effects with IM TXA because peak blood concentrations are lower than with the IV route. IM TXA also has practical advantages as it is quicker and simpler to administer. By avoiding the need for IV line insertion and a slow IV injection, IM administration would free up overstretched midwives and doctors to focus on looking after the mother and baby and expand access to timely TXA treatment. Trial registration ClinicalTrials.gov NCT05562609. Registered on 3 October 2022. ISRCTN Registry ISRCTN12590098. Registered on 20 January 2023. Pan African Clinical Trial Registry PACTR202305473136570. Registered on 18 May 2023.